Lifetime Prevalence of Nonspecific Low Back Pain in Adolescents: A Cross-sectional Epidemiologic Survey. (December 2021) - Masiero, Stefano; Sarto, Fabio; Cattelan, Manuela; Sarto, Diego; Del Felice, Alessandra; Agostini, Francesco; Scanu, Anna
Abstract : Background: Many nonconclusive studies have been conducted on low back pain (LBP) in adolescents and associated factors. Objective: The aim was to assess the lifetime prevalence and associated factors of LBP in adolescents. Materials and Methods: A questionnaire was administered in high school students (14–19-yr-old participants) in Veneto region (Italy). The self-administered, structured questionnaire included anthropometric data; psychologic factors and lifestyle; presence, intensity, and family history of LBP; referral to professional health care for LBP; and a short version of the International Physical Activity Questionnaire. Results: A total of 6281 adolescents were recruited; 5204 questionnaires were included in the final analysis. A total of 2549 (48.98%) students reported one or more LBP episodes and 723 (13.89%) reported nonspecific disabling lumbar pain (i.e., no underlying pathology); 1040 (41.11%) subjects with LBP consulted a healthcare professional. A significant association emerged for LBP with sex (female), positive family history, time spent sitting or using electronic devices, sleep deprivation (<5 hrs/night), and low level of physical activity. Conclusion: In a large sample of adolescents, LBP lifetime prevalence is high and often associated with disabling pain and sedentary lifestyle, requiring professional care. These findings may support the development of prevention and treatment strategies of LBP in adolescents, reducing the risk of developing chronic pain. Abstract : Supplemental digital content is available in the text.